(untitled) (Bangladesh Journal of Neurosurgery, 2019)
Cauda equina syndrome is reported as a complication in 0.2% - 1% following lumbar disc herniation . The pathophysiologic mechanism of this complication and its management is yet poorly understood. Though some factors has postulated in different studies. In this case, patient’s back pain and leg pain is satisfactorily improved with newly onset retention of urine followed by overflow incontinence and constipation after a single level lumbar discectomy. No abnormalities were seen on the postoperative imaging studies. This is a retrospective analysis of records and radiographs in a patient who developed acute bowel and bladder dysfunction after surgery for lumbar disc herniation. Bang. J Neurosurgery 2019; 9(1): 54-56